3 THE REVISED STATUTES, CODE AND GENERAL LAWS OF THE STATE OF NEW YORK 3330, § 3 (Clarence F. Birdseye ed., 1890) - (:unkn) unknown (General Publisher, 1890)
Anyone found carrying weapons is presumed to carry with intent to commit a crime.
--
Keywords: CARRY